The Implementation of Multisensory Techniques in a Project-Based Learning Model Integrating Local Wisdom to Promote Inclusive Education at MI Muhammadiyah 2 Kudus: Implementasi Teknik Multisensori dalam Model PJBL Bermuatan Kearifan Lokal untuk Mewujudkan Pendidikan Inklusif di Mi Muhammadiyah 2 Kudus - Yuliana Noor Annisa; Eva Luthfi Fakhru Ahsani (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
The lack of teachers' knowledge about the concept of inclusive education and their ability to establish appropriate techniques and methods has become an issue in the implementation of inclusive education. This research aims to provide insights on how to implement multisensory techniques in the PjBL learning model infused with local wisdom to achieve inclusive education at the third-grade level. This study employs a qualitative case study research method with teachers and 19 third-grade students of MI Muhammadiyah 2 Kudus as the research subjects. Data collection techniques were carried out using observation, interviews, questionnaires, field notes, and documentation. The research findings indicate that the implementation of multisensory techniques in the PjBL model infused with local wisdom can be successfully carried out. The results can lead to more active, engaging, and meaningful learning activities for the students. In addition, the learning can create an inclusive environment by enhancing active participation among students and providing equal opportunities and access.